Automation and demographic change - Ana Lucia Abeliansky; Klaus Prettner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
A standard theoretical framework of accumulation of traditional physical capital and automation capital predicts that countries with a lower population growth rate are the ones innovating/adopting new automation technologies faster. We test the model prediction using panel data for 60 countries from 1993 to 2013. Empirical estimates suggest that a 1% increase in population growth is associated with an approximate 2% reduction in the growth rate of robot density.
Keywords: J11; O14; O33; O40; 330